Relationship marketing in hotel industry: A conceptual study / Leena Nitin Fukey … [et a.l] - Fukey, Leena Nitin; Kumar, Jeetesh; Balasubramanian, Kandappan; Patil, Jyotsna A. (UiTM Press, 2016)
The appreciation of relationship marketing is in building and retaining long-standing relationships with customers, which has a huge impression for various organizations in the West. In any case, because of standards and ethnic modifications, the same term cannot be applied in the local context. This study is mainly drawn from the data collected through an online survey at five star hotels in the city of Bangalore. The purpose of this research is to draw the hoteliers’ attention about relationship marketing and propose the use of this term for the existing strategies currently used in hotels. The extensive literature review related to strategies practiced in the hotel industry supports the mapping of strategies into one distinguished term: Relationship Marketing. The primary aim of the study is to develop a framework based on literature for hoteliers to implement and practice the new term in the hotel industry. The study ends with a blueprint as well as recommendations in using the new term to enhance customer relationship and loyalty.